ANALISIS PENGARUH PENGELUARAN PEMERINTAH DI SEKTOR PENDIDIKAN DAN KESEHATAN TERHADAP PENGENTASAN KEMISKINAN MELALUI PENINGKATAN PEMBANGUNAN MANUSIA DI PROVINSI JAWA TENGAH - Widodo, Adi; Waridin, Waridin; Kodoatie, Johanna Maria (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2011)
The purposes of this paper are (a) to illustrate patterns of development of not only publicexpenditures on education and health sectors, indicators of human development, and poverty indicators inCentral Java province, (b) to identify and analyze the role of the Human Development Index (HDI) withregards to the relationship between government spending for education and health sectors and povertyreduction in the province: whether the HDI as a moderator variable or intervening variable. The data usedwere government expenditures in education and health sectors, HDI and regional poverty rates in 35 districts /cities in Central Java, in the period of 2007 to 2008. The study suggests that (a) in general, in the year 2007 and2008, government spending patterns in education and health sectors, HDI and the percentage of the numberof poor in the regencies / cities demonstrated a positive trend. That is, the increase in government spendingon education and health sectors was followed by not only an increase in HDI but also by a decrease in thepercentage of the population is the poor. Interestingly, the study suggests that HDI was more dominant to be aâ€œpure moderatorâ€ variable rather than to be an intervening variable. This infers that the relationship betweengovernment spending on education and health sectors and the alleviation of poverty is reinforced by the roleof HDI. Consequently, government spending on education and health sector did not by itself affect the povertyreduction directly.